You are on page 1of 20

KING’S GLORY EDUCATIONAL CENTRE

CE MOCK EXAMINATION 2004

ADDITIONAL MATHEMATICS
A. LEUNG

Suggested Answer

Prepared by A. Leung
King’s Glory Educational Centre
All Rights Reserved 2004
2004-CE-ADD.MATH-1

-1-
Additional Mathematics suggested solution

Section A

1. Let P(n) be the proposition.
n(n + 1)(n + 5)
P(n) : T1 + T2 + T3 + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ +Tn =
3
1(1 + 1)(1 + 5)
When n = 1, L.H.S. = T1 = 1(1 + 3) = 4 , R.H.S. = =4
3
∴ P (1) is true.

k (k + 1)(k + 5)
Assume P (k ) is true, i.e. T1 + T2 + T3 + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ +Tk =
3

When n = k + 1, L.H.S. = (T1 + T2 + T3 + ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ ⋅ +Tk ) + Tk +1

k (k + 1)(k + 5)
= + (k + 1)(k + 4)
3

k +1 2
=
3
(
k + 5k + 3k + 12 )

(k + 1)(k + 2)(k + 6)
=
3

∴ P (k + 1) is also true.

By the principle of mathematical induction, the proposition is true for all positive integers n.

r
th
2. The (r+1) term in descending powers of x = C 18
r (x )
2 18 − r ⎛2⎞
⎜ ⎟
⎝ x⎠

( )
= 2 r C r18 x 36−3r

For x 3 , power of x = 3, 36 − 3r = 3 , r = 11

Coefficient of x 3 = 211 C1118 = 65175552.

-2-
3. f ( x) = x 2 + (3 + m) x + (2m − 2) . Let A(α , 0) , B( β , 0) be the coordinates of intersection.

α , β are the roots of the equation x 2 + (3 + m) x + (2m − 2) = 0 .

α + β = −(3 + m) αβ = 2m − 2

α−β =2 5

(α − β )2 = 20

(α + β )2 − 4αβ = 20

[− (3 + m)]2 − 4αβ = 20

(m − 3)(m + 1) = 0

m=3 or m = −1

4. (2 x + 1)(y 3 − 2 y + 1) + (x 2 + x + 5)(3 y 2 − 2) dy = 0
dx

dy (2 x + 1) (y 3 − 2 y + 1)
=− 2
dx (x + x + 5)(3 y 2 − 2)
dy 3
=
dx (1, 0 ) 14

Equation of tangent is y =
3
(x − 1)
14

i.e. 3x − 14 y − 3 = 0

-3-
5. (a) I = ∫ 15 cos 4 θ (cosθ dθ )

Let t = sin θ , dt = cosθ dθ

I = ∫ 15(1 − t 2 ) 2 dt

∫ 15(1 − 2t + t 4 ) dt
2
=

= 15t − 10t 3 + 3t 5 + c

= 15 sin θ − 10 sin 3 θ + 3 sin 5 θ + c

dy
(b) y=∫ dx
dx

∫ 15 cos
5
= x dx

= 15 sin x − 10 sin 3 x + 3 sin 5 x + c

π
When x = ,y=6
2

15 − 10 + 3 + c = 6

c = −2

Equation of C is y = 3 sin 5 x − 10 sin 3 x + 15 sin x − 2

-4-
3
6. (a) tan 2θ =
4

2 tan θ 3
=
1 − tan θ 4
2

8 tan θ = 3 − 3 tan 2 θ

3 tan 2 θ + 8 tan θ − 3 = 0

(3 tan θ − 1)(tan θ + 3) = 0

1
tan θ = (tan θ > 0)
3

r
(b) tan θ =
h

1
r= h
3

1
V = πr 2 h
3

2
1 ⎛1 ⎞
= π ⎜ h⎟ h
3 ⎝3 ⎠

π
= h3
27

Differentiate both sides with respect to time t,

dV π ⎛ 2 dh ⎞
= ⎜ 3h ⎟
dt 27 ⎝ dt ⎠

-5-
π dh
= h2
9 dt

dV
Now, h = 8 , = 40π
dt

π
40π =
9
( 8 )
2 dh
dt

dh 45
=
dt 8

45
water level is increasing at cm / min at that instant.
8

7. 2 cos 5 x cos 2 x = 3 cos 5 x

cos 5 x(2 cos 2 x − 3 ) = 0

3
cos 5 x = 0 or cos 2 x =
2

5 x = (2m + 1) 90 o or 2 x = 360 o n ± 30 o where m, n are integers.

x = (2m + 1)18 o or x = 180 o n + 15 o

-6-
m−4 2
8. (a) = where m is the slope of the required line.
1 + 4m 9

9m − 36 = 2 + 8m or 9m − 36 = −2 − 8m

m = 38 or m=2

⎛ 1+ k ⎞
(b) − ⎜ ⎟=2 (m < 3)
⎝ 7 − 2k ⎠

1 + k = −14 + 4k

k =5

Equation of required line is 6 x − 3 y − 17 = 0

10k + 3 v 4k + 11 v
9. (a) OP = i+ j
1+ k 1+ k

v v
(b) AB = 7i − 7 j

Q OP ⊥ AB , OP ⋅ AB = 0

⎛ 10k + 3 v 4k + 11 v ⎞ v v
⎜ i+ j ⎟ ⋅ (7i − 7 j ) = 0
⎝ 1+ k 1+ k ⎠

-7-
7
[(10k + 3)(1) − (4k + 11)(1)] = 0
1+ k

6k − 8 = 0

4
k=
3

v v v v
(c) OP = 7i + 7 j , OA = 3 i + 11 j

OP ⋅ OA = OP OA cos ∠AOP

v v v v
(7i + 7 j ) ⋅ (3 i + 11 j ) = 7 2 + 7 2 3 2 + 112 cos ∠AOP

(7)(3) + (7)(11) = 98 130 cos ∠AOP

∠AOP = 29.7 o

-8-
10. (a) Maximum point : (−1, 3) Minimum point : (1, − 3)

(b)

11. Q ( x + 3) 2 = x + 3
2

∴ x+3 − 7 x + 3 − 18 ≤ 0
2

( x + 3 − 9 )( x + 3 − 2 ) ≤ 0

x+3 ≤9 (Q x + 3 + 2 ≥ 2 )

−9 ≤ x+3≤ 9

− 12 ≤ x ≤ 6

-9-
Section B
12. (a) (i) Equation of S1 is x( x + 2) + ( y − 2)( y + 2) = 0

i.e. x 2 + y 2 + 2 x − 4 = 0

2 − (− 2)
(ii) Equation of BC is y + 2 = (x − 0)
−2

i.e. 2x + y + 2 = 0

(iii) Equation of family of circle through B and C is

x 2 + y 2 + 2 x − 4 + k (2 x + y + 2) = 0 for all values of k.

the circle passes through A(3, 7)

∴ 9 + 6 + 49 − 4 + k (6 + 7 + 2 ) = 0

k = −4

∴ Equation of S 2 is x 2 + y 2 − 6 x − 4 y − 12 = 0

(b) (i) Equation of tangent is y = mx + 8

⎧ x 2 + y 2 − 6 x − 4 y − 12 = 0
⎨ have equal roots
⎩ y = mx + 8

On substituting y, we have

(1 + m )x
2 2
+ 2(6m − 3)x + 20 = 0

∴ [2(6m − 3)]2 − 4(1 + m 2 )(20) = 0

-10-
On simplifying, giving 16m 2 − 36m − 11 = 0

9 11
∴ m1 + m2 = , m1 m2 = −
4 16

m1 − m2
(ii) tan θ =
1 + m1 m2

(m1 + m2 )2 − 4m1m2
=
1 + m1 m2

⎛ − 11 ⎞
2
⎛9⎞
⎜ ⎟ − 4⎜ ⎟
⎝4⎠ ⎝ 16 ⎠
=
11
1−
16

= 4 5

⎧y = x2
13. (a) For intersection of P and L, ⎨
⎩ y = ax

On solving, we have x = 0 or x = a

a
Hence ∫ 0
(ax − x 2 ) dx = 288

a
⎡a 2 1 3 ⎤
⎢ 2 x − 3 x ⎥ = 288
⎣ ⎦0

a3 a3
− = 288
2 3

a = 12

-11-
(b) Required volume

= π∫
12

0
[(12 x + 1) 2
− ( x 2 + 1) 2 dx ]

12
= π∫ (− x 4 + 142 x 2 + 24 x) dx
0

12
⎡ 1 142 3 ⎤
= π ⎢− x 5 + x + 12 x 2 ⎥
⎣ 5 3 ⎦0

⎡ 1 142 ⎤
= π ⎢− (12) 5 + (12) 3 + 12(12) 2 ⎥
⎣ 5 3 ⎦

= 33753.6 π

h
(c) Capacity of bowl = π ∫ x 2 dy
0

h
= π ∫ y dy
0

h
⎡ y2 ⎤
=π ⎢ ⎥
⎣ 2 ⎦0

πh 2
=
2

πh 2
(d) = 33753.6 π
2

h = 260

-12-
π
14. (a) V = (l sin θ ) 2 (l cosθ )
3
πl 3 ⎛ π⎞
= sin 2 θ cosθ ⎜0 < θ < ⎟
3 ⎝ 2⎠

dV πl 3
(b)

=
3
[
sin 2 θ (− sin θ ) + cosθ (2 sin θ cosθ ) ]

πl 3
=
3
(
sin θ 2 − 3 sin 2 θ )

πl 3
When V is increasing,
dV

> 0,
3
( )
sin θ 2 − 3 sin 2 θ > 0

2 ⎛ π⎞
sin 2 θ < ⎜0 < θ < ⎟
3 ⎝ 2⎠
6
sin θ <
3

πl 3
When V is decreasing,
dV

< 0,
3
( )
sin θ 2 − 3 sin 2 θ < 0

2 ⎛ π⎞
sin 2 θ > ⎜0 < θ < ⎟
3 ⎝ 2⎠
6
sin θ >
3

6
Since V changes from increasing to decreasing via sin θ = , hence when V is
3
6
maximum, sin θ = .
3

1
S= (2l sin θ )(l cosθ )
2

1 2
= l sin 2θ
2

Clearly, S is maximum when sin 2θ = 1 ,

-13-
π π
2θ = , i.e. θ =
2 4

Therefore, when V is a maximum, S is not a maximum.

π dθ
(d) When l = 6, θ = , = 0.1
6 dt

dV π ⎡ π π⎤
= (6) 3 ⎢2 sin − 3 sin 3 ⎥
dθ 3 ⎣ 6 6⎦

= 45π

dV dV dθ
Q = ⋅
dt dθ dt

dV
= (45π )(0.1) = 4.5π .
dt

Hence the capacity is increasing at 4.5π unit 3 per second

-14-
v v v 2
15. (a) a ⋅ a = a =1,

v v v v ⎛1⎞
a ⋅ b = a b cosθ = (1)(3)⎜ ⎟ = 1
⎝ 3⎠

v v v 2
b ⋅b = b =9

v v
a + 2b
(b) OC =
3

v v
(k + 1)a + (2k + 2)b
(c) OD =
3

BD = OD − OB

v v
(k + 1)a + (2k + 2)b v
= −b
3

v v
(k + 1)a + (2k − 1)b
=
3

Q OD⊥BD , ∴ OD ⋅ BD = 0

( )⎤⎥ ⋅ 13 [(k + 1)av + (2k − 1)b ] = 0
⎡k +1 v v v
⎢⎣ 3 a + 2b

k +1
9
[ v v v v v v v v
]
(k + 1)a ⋅ a + (2k − 1)a ⋅ b + 2(k + 1)b ⋅ a + 2(2k − 1)b ⋅ b = 0

(k + 1)(1) + (2k − 1)(1) + 2(k + 1)(1) + 2(2k − 1)(9) = 0

41k = 16

16
k=
41

-15-
( )
1 v v
BD = 19a − 3b
41

( )⎤⎥ ⋅ ⎡⎢ 411 (19av − 3b )⎤⎥ ⋅
⎡1 v v v
BD ⋅ BD = ⎢ 19a − 3b
⎣ 41 ⎦ ⎣ ⎦

(
v v
)
⎛1⎞
2
2
v v v v
BD = ⎜ ⎟ 361a ⋅ a − 114a ⋅ b + 9b ⋅ b
⎝ 41 ⎠

2
⎛1⎞
= ⎜ ⎟ [361(1) − 114(1) + 9(9)]
⎝ 41 ⎠

2 2 32
BD = 82 , ∴ BD = 82
41 41

(e)
v v v
(
AO ⋅ AB = − a ⋅ b − a )
v v v v
= a ⋅a − a ⋅b

= 1−1 = 0

∠OAB = 90 o , hence ∠OAB = ∠ODB = 90 o

Therefore, OADB is a cyclic quadrilateral

-16-
16. (a) (i) Let f ( x) = ax 3 + bx 2 + cx + d .

Since α is a root of f ( x) = 0 , ∴ x − α is a factor of f ( x) .

Similarly , x − β and x − γ is a factor of f ( x)

Hence f ( x) = a( x − α )( x − β )( x − γ )

ax 3 + bx 2 + cx + d ≡ a( x − α )( x − β )( x − γ )

≡ ax 3 − a(α + β + γ ) x + a(αβ + αγ + βγ ) − aαβγ

Comparing coefficients of appropriate terms, we have

c
a(αβ + αγ + βγ ) = c , αβ + αγ + βγ =
a

−d
− a(αβγ ) = d , αβγ
a

(b) cos 3θ = cos(θ + 2θ )

= cosθ cos 2θ − sin θ sin 2θ

= cosθ (2 cos 2 θ − 1) − sin θ (2 sin θ cosθ )

= cosθ (2 cos 2 θ − 1) − 2 cosθ (1 − cos 2 θ )

= 4 cos 3 θ − 3 cosθ

Let x = cosθ , 8 cos 3 θ − 6 cosθ = 3

3
4 cos 3 θ − 3 cosθ =
2
3
cos 3θ =
2

3θ = 30 o , 330 o , 390 o

-17-
θ = 10 o , 110 o , 130 o

(c) cos10 o , cos110 o and cos130 o are the roots of 8 x 3 − 6 x − 3 = 0

⎛− 3⎞
(i) cos10 o cos110 o cos130 o = − ⎜⎜ ⎟

⎝ 8 ⎠

( )(
cos10 o − cos 70 o − cos 50 o ) =
8
3

3
cos10 o cos 50 o cos 70 o =
8

−6
(ii) cos10 o cos130 o + cos10 o cos110 o + cos110 o cos130 o =
8

−3
=
4

-18-
17. (i) α + β = −4 , αβ = 2

S1 = α + β = −4

S2 = α 2 + β 2

= (α + β ) − 2αβ
2

= 12

(ii) Q α , β are the roots of the equation x 2 + 4 x + 2 = 0

∴ S n + 2 + 4S n +1 + 2 S n

( ) ( ) (
= α n + 2 + β n + 2 + 4 α n +1 + β n +1 + 2 α n + β n )
( )
= α n α 2 + 4α + 2 + β n ( β 2 + 4 β + 2)

=0

(iii) Put n = 1, S 3 + 4 S 2 + 2 S1 = 0

S 3 + 4(12) − 2(− 4 ) = 0

S 3 = −40

Put n = 2, S 4 + 4S 3 + 2S 2 = 0

S 4 + 4(− 40 ) + 2(12 ) = 0

S 4 = 136

-19-
(iv) Put n = 3, S 5 + 4S 4 + 2S 3 = 0

S 5 + 4(136) + 2(− 40) = 0

S 5 = −464

Since x 2 + 4 x + 2 = 0

− 4 ± 4 2 − 4(1)(2)
x=
2(1)

x = −2 + 2 or x = −2 − 2

Q S 5 = −464

(
∴ −2+ 2 + −2− 2 ) (
5
)
5
= −464

(
− 2− 2 − 2+ 2) (
5
)
5
= −464

(2 − 2 ) + (2 + 2 )
5 5
= 464

-20-